2020
DOI: 10.1038/s41598-020-67790-0
|View full text |Cite
|
Sign up to set email alerts
|

Silencing miR-370-3p rescues funny current and sinus node function in heart failure

Abstract: Bradyarrhythmias are an important cause of mortality in heart failure and previous studies indicate a mechanistic role for electrical remodelling of the key pacemaking ion channel HCN4 in this process. Here we show that, in a mouse model of heart failure in which there is sinus bradycardia, there is upregulation of a microRNA (miR-370-3p), downregulation of the pacemaker ion channel, HCN4, and downregulation of the corresponding ionic current, I f , in the sinus node. In vitro, exogenous miR-370-3p inhibits HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 98 publications
1
39
0
Order By: Relevance
“…The authors suggested that conjoint upregulation of RyR3 and calsequestrin 2 might however inhibit Ca 2+ release resulting in slow automaticity. More recently, the same group (Yanni et al, 2020) reported that pressure overload-induced HF in mice did not change SAN mRNA for various components of the "Ca 2+ clock, " including RyR2, SERCA, calsequestrin, and NCX. This is consistent with a study in isolated SAN cells from rabbit HF model of pressure and volume overload, which concluded that SAN Ca 2+ cycling properties are conserved despite bradycardic effects (Verkerk et al, 2015).…”
Section: Ryr2 and Sinus Node Dysfunctionmentioning
confidence: 96%
“…The authors suggested that conjoint upregulation of RyR3 and calsequestrin 2 might however inhibit Ca 2+ release resulting in slow automaticity. More recently, the same group (Yanni et al, 2020) reported that pressure overload-induced HF in mice did not change SAN mRNA for various components of the "Ca 2+ clock, " including RyR2, SERCA, calsequestrin, and NCX. This is consistent with a study in isolated SAN cells from rabbit HF model of pressure and volume overload, which concluded that SAN Ca 2+ cycling properties are conserved despite bradycardic effects (Verkerk et al, 2015).…”
Section: Ryr2 and Sinus Node Dysfunctionmentioning
confidence: 96%
“…In the sinus node, evidence suggests dysfunction and downregulation of I f in HF [9,10,162,163] which may cause bradyarrhythmia in certain situations. In contrast, in the ventricle, I f is upregulated (Figure 9) [164][165][166] which was attributed to enhanced mRNA and protein expressions of HNC2 and HCN4 channels in the failing human ventricle [167].…”
Section: Changes Of the Pacemaker Current (I F ) In Hfmentioning
confidence: 99%
“…Finally, extensive linkage and genome-wide associated studies [18,[45][46][47][48][49][50][51][52], posttranscriptional analyses, and next-generation sequencing [49,[53][54][55][56][57][58][59][60][61][62] on animal and human tissues and cells, included pluripotent stem cells [63,64], shed light on the ontology of the genes regulated during CCS development and physiology, as well as on their fine-tune silencing provided by specific microRNAs (e.g., miR-1 and miR-128a). Each component of the CCS is, hence, the developmental embryology result of unique hierarchical transcriptional networks, with a prominent orchestrating or ruling role by T-box transcription factors, as previously summarized by Munshi in 2012 [65].…”
Section: The Embryological Development Anatomy and Physiology Of The Heart Rhythmmentioning
confidence: 99%